2020
DOI: 10.1371/journal.pone.0231812
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt ion interaction with TMEM16A calcium-activated chloride channel: Inhibition and potentiation

Abstract: TMEM16A, a Ca 2+-sensitive Clchannel, plays key roles in many physiological functions related to Cltransport across lipid membranes. Activation of this channel is mediated via binding intracellular Ca 2+ to the channel with a relatively high apparent affinity, roughly in the sub-μM to low μM concentration range. Recently available high-resolution structures of TMEM16 molecules reveal that the high-affinity Ca 2+ activation sites are formed by several acidic amino acids, using their negatively charged sidechain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…Of note, the inner filter effect due to the absorbance of 5 mM Co 2+ in the wavelength range 470–550 nm, calculated as indicated in the Materials and Methods section, can only account for less than 5% quenching of this fluorescence. Co 2+ is a well calcium channel blocker at millimolar concentration, and has also been shown to bind to Ca 2+ sites in proteins (see for example [ 53 , 54 ]). Co 2+ has a R 0 value of 1.2 nm as the FRET acceptor of the green fluorescence of fluorescein [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the inner filter effect due to the absorbance of 5 mM Co 2+ in the wavelength range 470–550 nm, calculated as indicated in the Materials and Methods section, can only account for less than 5% quenching of this fluorescence. Co 2+ is a well calcium channel blocker at millimolar concentration, and has also been shown to bind to Ca 2+ sites in proteins (see for example [ 53 , 54 ]). Co 2+ has a R 0 value of 1.2 nm as the FRET acceptor of the green fluorescence of fluorescein [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that intracellular Co 2+ (up to 20 mM) by itself does not activate current in WT 16A . However, intracellular Co 2+ potentiates the Ca 2+ -induced WT 16A current, followed by an inhibition effect [ 38 ]. Co 2+ inhibition on the WT 16A current (see Figure 1 A) is easier to understand—Co 2+ competes with intracellular Ca 2+ for the high-affinity Ca 2+ -activation sites [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, intracellular Co 2+ potentiates the Ca 2+ -induced WT 16A current, followed by an inhibition effect [ 38 ]. Co 2+ inhibition on the WT 16A current (see Figure 1 A) is easier to understand—Co 2+ competes with intracellular Ca 2+ for the high-affinity Ca 2+ -activation sites [ 38 ]. The current potentiation by Co 2+ , however, is a different mechanism because the potentiation occurs before the inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations